THE EFFECTIVENESS OF A PROPOSED COUNSELLING PROGRAM FOR INCREASING THE LEVEL OF SELF-REGULATED LEARNING AMONG UNIVERSITY STUDENTS - Mustafa , Khalid; Ahmed, Zhakaw (Humanities Journal of University of Zakho, 2025)
This study aims to develop a proposed counseling program to enhance self-regulated learning among university students and to examine the program’s effectiveness within the experimental group based on gender, through a comparison of pre-test and post-test scores. The study also seeks to determine the overall effectiveness of the program and measure its effect size. The experimental method was employed as the most suitable approach for achieving these objectives.The research was conducted with first-year students at the University of Raparin. The study sample consisted of 43 first-year students from the Department of Computer Science. The equivalence of key variables such as motivation, intelligence, attitudes toward the field of study, family income, university entrance grade point average, and age was established. A total of 24 students were then selected and randomly assigned to an experimental group and a control group. To assess outcomes, the study developed a self-regulated learning scale and applied psychometric procedures to ensure its validity and reliability. Statistical analysis was conducted using SPSS. The results revealed that the program had a positive impact on the experimental group by significantly increasing their level of self-regulated learning. The program also demonstrated a high effect size across the sample as a whole. Furthermore, gender differences were found to have no significant effect on self-regulated learning levels.